2020
DOI: 10.1051/0004-6361/201936177
|View full text |Cite
|
Sign up to set email alerts
|

Optical and near-infrared observations of the Fried Egg Nebula

Abstract: Context. The fate of a massive star during the latest stages of its evolution is highly dependent on its mass-loss rate and geometry and therefore knowing the geometry of the circumstellar material close to the star and its surroundings is crucial. Aims. We aim to provide insight into the nature (i.e. geometry, rates) of mass-loss episodes, and in particular, the connection between the observed asymmetries due to the mass lost in a fast wind or during a previous, prodigious mass-losing phase. In this context, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 92 publications
(130 reference statements)
3
26
1
Order By: Relevance
“…Notably, at high accretion rates (M acc >=10 −3 M ⊙ /yr), the accreting MYSO is expected to be bloated (Hosokawa et al 2010), and therefore cool, which can arguably prevent the direct ionisation of the disc. However, Simon et al (1983) showed that winds of MYSOs can be so dense that hydrogen is collisionally excited to its n=2 state, which makes its ionisation from cooler stars possible (see also, Koumpia et al 2020;Drew et al 1998;Drew 1998). Indeed, a bloated star could also explain the narrow single line profiles of Brγ observed in MYSOs in various studies (e.g., Pomohaci et al 2017), which is in contrast to the relatively broader and double-peaked lines predicted by disc models around hot main sequence stars (Sim et al 2005).…”
Section: Origin Of the Brγ Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, at high accretion rates (M acc >=10 −3 M ⊙ /yr), the accreting MYSO is expected to be bloated (Hosokawa et al 2010), and therefore cool, which can arguably prevent the direct ionisation of the disc. However, Simon et al (1983) showed that winds of MYSOs can be so dense that hydrogen is collisionally excited to its n=2 state, which makes its ionisation from cooler stars possible (see also, Koumpia et al 2020;Drew et al 1998;Drew 1998). Indeed, a bloated star could also explain the narrow single line profiles of Brγ observed in MYSOs in various studies (e.g., Pomohaci et al 2017), which is in contrast to the relatively broader and double-peaked lines predicted by disc models around hot main sequence stars (Sim et al 2005).…”
Section: Origin Of the Brγ Emissionmentioning
confidence: 99%
“…Wanting to limit the algorithm dependency on the reconstructed images, we proceed to a thorough comparison of WISARD with the Multi-aperture ImageReconstruction Algorithm (MIRA; Thiébaut 2008) and BSMEM (Baron & Young 2008). A detailed description of the initialisation of the image reconstruction algorithms is presented in Koumpia et al (2020).…”
Section: Appendix A: Observations Appendix B: Image Reconstructionmentioning
confidence: 99%
“…Moreover, multidimensional calculations including a local treatment of the radiative acceleration in the stellar envelope, and hydrodynamic wind models able to investigate the complex radiative acceleration in the supersonic outflows (Sundqvist et al 2019;Sander et al 2020;Björklund et al 2020), can give insights into the ability of our scenario to reproduce the observed phenomenology of these massive stars. Furthermore, our models establish the framework required for quantitative predictions on the formation of circumstellar nebulae surrounding LBVs (Nota et al 1995;Weis 2003;Agliozzo et al 2014), due to wind-wind interaction and variable mass-loss rates (Vink & de Koter 2002;Koumpia et al 2020), as well as their imprint on supernovae (Chevalier & Fransson 1994;Kotak & Vink 2006;Boian & Groh 2018).…”
Section: Discussionmentioning
confidence: 66%
“…giants as an empirical limit for the triggering of the S Dor instability (Smith et al 2004;Davies et al 2018), as well as the formation of shells and nebulae due to the changing wind properties (e.g., Koumpia et al 2020). For post-main-sequence stars, we expect a significantly lower initial-mass limit because the L/M is higher (higher by more than an order of magnitude than the main-sequence) reached in the late phases of stellar evolution (Brott et al 2011;Langer 2012).…”
Section: Appendix B: Sonic-point Diagrammentioning
confidence: 96%
“…Here we discuss the effects of reduced mass loss on our results, by replacing the standard RSG metallicity-independent mass-loss rates of de Jager with the Fe-dependent recipe of Vink et al (2001) in the yellow supergiant regime (5500 K < 𝑇 eff < 10 kK). The mass loss in the YSG regime are highly uncertain (see Lobel et al 2003;Gordon & Humphreys 2019;Andrews et al 2019;Koumpia et al 2020;Grassitelli et al 2021) and understanding the variation of mass loss as a function of effective temperature is crucial. The RSG rates by de Jager are still used for cooler temperatures.…”
Section: Effect Of Mass Lossmentioning
confidence: 99%